Semiognennaia strela - Alexandrow, Evgeny; Danilko, Elena (Russia, 2009)
For centuries Finno-Ugric and Slavic peoples have been living on the land of Perm and Vyatka. What is the present of the descendants of these ancient cultures? How do they identify themselves – are they Permyaks or Russians?
Verzio Film Festival Submission
Keywords: Documentary films